(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This thesis examines the theoretical foundations of teaching methods designed to develop students’ cognitive activity, drawing on cognitive psychology and constructivist learning theory. In contemporary education, learners are viewed not as passive recipients of knowledge, but as active participants who construct understanding through independent inquiry, a key indicator of educational quality. Implementing instructional strategies that actively engage students’ cognitive processes is therefore essential. Identifying theoretically and empirically grounded approaches that foster critical thinking, curiosity, and creativity remains a major pedagogical and methodological challenge.